2019
DOI: 10.1186/s12906-019-2464-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on Th17 cell-related immune responses under tacrolimus-based immunosuppression

Abstract: Background We previously reported that tacrolimus (Tac) does not decrease T helper 17 cells (Th17) response in kidney transplantation. In this study, we evaluated whether Resveratrol (Resv) has immunosuppressive effects by decreasing Th17 responses in Tac-based immunosuppression. Methods We investigated the effects of Resv under Tac-treatment conditions, on CD4 + T cell differentiation to Th17 cells in peripheral blood mononuclear cells (PBMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Inhibition of allergic contact dermatitis by resveratrol could be attributable to the downregulation of interferon regulatory factor 1/ STAT1 signaling pathway and inhibition of phosphorylation of MAPK/p38 and/or phospholipase Cc [113,116,198]. Moreover, resveratrol inhibited proliferation and differentiation of CD+ T cells and proliferation of 17 T cells via upregulation of phosphorylated MAPK and downregulation of phosphorylated mammalian target of rapamycin (p-mTOR) in Jurkat cells [199]. Furthermore, resveratrol-induced inhibition of TNFα-induced cytokine production in fibroblasts is via activation of SIRT1 because knockdown of SIRT1 abolishes the inhibitory effect resveratrol on inflammation [200].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Inhibition of allergic contact dermatitis by resveratrol could be attributable to the downregulation of interferon regulatory factor 1/ STAT1 signaling pathway and inhibition of phosphorylation of MAPK/p38 and/or phospholipase Cc [113,116,198]. Moreover, resveratrol inhibited proliferation and differentiation of CD+ T cells and proliferation of 17 T cells via upregulation of phosphorylated MAPK and downregulation of phosphorylated mammalian target of rapamycin (p-mTOR) in Jurkat cells [199]. Furthermore, resveratrol-induced inhibition of TNFα-induced cytokine production in fibroblasts is via activation of SIRT1 because knockdown of SIRT1 abolishes the inhibitory effect resveratrol on inflammation [200].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Application of resveratrol resulted in reduced phosphorylation of mTOR in a dose-dependent manner. 67 This study provides an important reminder that the mTOR pathway plays a key role in T cell differentiation, and therefore in the immune response.…”
Section: Resveratrolmentioning
confidence: 88%
“…Th17 cells mainly secrete IL‐22, and resveratrol can reduce IL‐22 levels through Th17 cells (Doh et al . 2019). Previous study has shown that resveratrol upregulates JNK signalling pathway and reduces cytokine‐induced hepatocyte iNOS (Kimbrough et al .…”
Section: Discussionmentioning
confidence: 99%